Therapeutic monoclonal antibodies for Ebola virus infection derived from vaccinated humans - Rijal, P; Elias, SC; Machado, SR; Xiao, J; Schimanski, L; O'Dowd, V; Baker, T; Barry, E; Mendelsohn, SC; Cherry, CJ; Jin, J; Labbé, GM; et al. (Cell Press, 2019)
We describe therapeutic monoclonal antibodies isolated from human volunteers vaccinated with recombinant adenovirus expressing Ebola virus glycoprotein (EBOV GP) and boosted with modified vaccinia virus Ankara. Among 82 antibodies isolated from peripheral blood B cells, almost half neutralized GP pseudotyped influenza virus. The antibody response was diverse in gene usage and epitope recognition. Although close to germline in sequence, neutralizing antibodies with binding affinities in the nano- to pico-molar range, similar to “affinity matured” antibodies from convalescent donors, were found. They recognized the mucin-like domain, glycan cap, receptor binding region, and the base of the glycoprotein. A cross-reactive cocktail of four antibodies, targeting the latter three non-overlapping epitopes, given on day 3 of EBOV infection, completely protected guinea pigs. This study highlights the value of experimental vaccine trials as a rich source of therapeutic human monoclonal antibodies.